AN AHP APPLICATION TO EVALUATE SCORING CRITERIA FOR FAILURE MODE AND EFFECT ANALYSIS (FMEA) - Dimas Campos de Aguiar; Helder José Celani de Souza; Valério Antônio Pamplona Salomon (2010)
The Failure Mode and Effect Analysis (FMEA) has been developed by several researchers who have proposed distinct reference tables to score the Severity, Occurrence and Detection of a failure. This paper aims to evaluate, using AHP, several proposals for the application of Process FMEA, as well as to obtain and offer recommendations for its application. Five reference tables for Severity, six tables for Occurrence, and six tables for Detection are presented. These reference tables are evaluated for their application in the Brazilian automotive industry by using critical analysis and proper judgments. The scientific contribution of this paper is to provide a way to select a reference table, available in the FMEA literature, for the application of the FMEA process. http://dx.doi.org/10.13033/ijahp.v2i1.69